2023
DOI: 10.3390/soilsystems7020044
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Enhance Growth and Increase Concentrations of Anthocyanin, Phenolic Compounds, and Antioxidant Activity of Black Rice (Oryza sativa L.)

Abstract: Black rice (Oryza sativa L.) contains high concentrations of bioactive compounds that are associated with human-health benefits. Arbuscular mycorrhizal fungi (AMF) can increase plant performance and concentrations of these bioactive compounds. In a pot experiment, the effects of four different species of AMF (Claroideoglomus etunicatum; Rhizophagus variabilis; Rhizophagus nov. spec.; Acaulospora longula) were assessed on growth performance, grain yield, concentrations of phenolic compounds and anthocyanin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The upregulation of anthocyanin biosynthesis in black rice as a consequence of AMF symbiosis has also been reported by Tisarum et al [44] and Wangiyana et al [45]. A previous study on Maled Phai black rice cultivar has shown that AMF-inoculated plants exhibit higher productivity and concentrations of phytochemicals compared with non-mycorrhizal plants [14]. In the current study, the presence of AMF remarkably improved the root dry weight, grain weight, antioxidants, and anthocyanin, compared with non-inoculated plants.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The upregulation of anthocyanin biosynthesis in black rice as a consequence of AMF symbiosis has also been reported by Tisarum et al [44] and Wangiyana et al [45]. A previous study on Maled Phai black rice cultivar has shown that AMF-inoculated plants exhibit higher productivity and concentrations of phytochemicals compared with non-mycorrhizal plants [14]. In the current study, the presence of AMF remarkably improved the root dry weight, grain weight, antioxidants, and anthocyanin, compared with non-inoculated plants.…”
Section: Discussionsupporting
confidence: 66%
“…The AMF used in this study were molecularly identified as Rhizophagus variabilis strain KS-02 [14]. They was obtained from the Mycorrhiza and Mycotechnology Laboratory, Department of Microbiology, Faculty of Science, Khon Kaen University, Thailand.…”
Section: Amf Inoculum Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The commercial Rhizophagus irregularis products have shown positive, but less consistent yield results, which are often contributed to inconsistencies in viable AMF spores in products that are stored and shipped over long distances (Corkidi et al., 2004; Faye et al., 2013; Salomon et al., 2022). In addition to the success of AMF inoculation in bolstering yield, additional benefits of AMF inoculation on plant nutritional quality include increases in mineral nutrient uptake (Chandrasekaran, 2020; Clark & Zeto, 2000), anthocyanin concentration (Avio et al., 2017; Baslam et al., 2011; Chiomento et al., 2019; Nacoon et al., 2023; Tisarum et al., 2019), and overall antioxidant activity across a range of vegetables and fruits (Hart et al., 2015; Mollavali et al., 2016; Toussaint et al., 2007). Increases in the mineral nutrient concentration of foods can improve public health by preventing nutrient deficiency which affects over 2 billion people worldwide (Tulchinsky, 2010).…”
Section: Introductionmentioning
confidence: 99%